1968
DOI: 10.1104/pp.43.3.351
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Indoleacetic Acid and Gibberellic Acid in Leaf Abscission Control

Abstract: Abstract. Debladed midribs of citrus leaves showed the typical delay of abscission in response to indoleacetic acid (IAA), and the typical acceleration of abscission in response to gibberellic acid (GA). Interaction experiments with these 2 hormones indicated that the balance of the 2 hormones may be more important in regulating abscission than the quantity of either. The often reported acceleration of abscission with low quantities of IAA did not seem to exist in citrus. IAA did accelerate abscission in this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
14
0

Year Published

1968
1968
2008
2008

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…The data in Figure 1 agree with previous work from this (10) and other laboratories (15,17), that there is a fixed period of time in which IAA can be added to an explant and inhibit abscission.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The data in Figure 1 agree with previous work from this (10) and other laboratories (15,17), that there is a fixed period of time in which IAA can be added to an explant and inhibit abscission.…”
Section: Discussionsupporting
confidence: 82%
“…2,4-Dichlorophenoxyacetic acid, which is not destroyed or conjugated by this system, did not lose its ability to inhibit abscission. It was concluded that indole-3-acetic acid destruction is one of the processes involved in the aging stage of abscission in explants.Indoleacetic acid has been demonstrated to effectively inhibit abscission in many plant systems if it is applied to the distal cut surface of petioles (10,14,15,17). The applied auxin has been supposed to replace the continuous auxin supply from the leaf (14,20).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The potential of hormones such as auxin and gibberell,in to act as effector sulbstances (5,16) th,at conitrol repression and derepression o.f different pants of the genome and their involvement in abscission control (2,12) led us to look at the effect of these hormones on the rate of protein synthesis in the tissue associated with abscission. This paper demonstrates the biochemical distinctiveness with respect to protein synthesis of the abscission zone from the adjacenit tissue.…”
mentioning
confidence: 99%
“…Usually, however, these data do not show as great a magnitude of stimulation by auxin (6,7,11) as with bean, and in some cases no stimulation was observed (2,5,(9)(10)(11)(12) phase response to auxin in abscission has been conclusively found only in beans. In reviewing the effects of auxin in abscission, Jacobs has questioned the importance of the stimulatory role of auxin (8).…”
mentioning
confidence: 96%